P152 Recognition of LGV lymphadenitis in MSM. (30th June 2016) - Dosekun, Olamide; Simons, Rebecca; Iveson, Helen; Conway, Katie; White, John
Abstract : Background: There is a sustained high rate of lymphogranuloma venereum (LGV) amongst men who have sex with men (MSM) in the UK, with the highest annual number of diagnoses reported in 2015, yet prompt diagnosis of LGV, particularly from non-rectal sites, eludes clinicians. Aims: We present 4 cases highlighting the ongoing challenge of recognition of LGV lymphadenitis, particularly outside GUM settings, and challenges with diagnosis and management. Case reports: 4 MSM (3 with well-controlled HIV on antiretroviral therapy, 1 HIV negative) presented to their GPs with unilateral groin swellings, and were referred to haematology or surgical teams for investigation. Investigations included ultrasound, CT/MRI of the groin as well as fine needle aspiration, and in 2 cases surgical exploration followed by node excision. None of the patients had symptomatic proctitis, and triple-site NAAT swabs for Chlamydia trachomatis (CT) were negative, although 1 patient had previously diagnosed but untreated urethral CT one month prior. In 1 case, CT serology (WIF) showed a high L2 titre of >1:4000. In all cases, a 21-day course of doxycycline was commenced between 10–45 days from initial presentation. There was slow resolution of the lymphadenitis in 2 patients, necessitating a prolonged course of doxycycline (5 weeks), and addition of 7days of azithromycin 500mg once daily, respectively. Conclusion: Early recognition and management, including prompt aspiration/drainage of buboes and appropriate antibiotic treatment are key to management of LGV lymphadenitis. Poor penetration of antibiotics into abscesses and residual inflammation may delay clinical resolution compared to proctitis cases.